Assessment method and comparison method for cycling stability of negative electrode material

By performing short-cycle cycle step tests and data fitting in lithium-ion batteries to evaluate and compare the cycle stability of the negative electrode material, the problem of difficulty in effectively evaluating and comparing the cycle stability of the negative electrode material in the prior art is solved, and lossless and fast cycle stability evaluation and comparison is achieved.

CN119511121APending Publication Date: 2025-02-25JIANGSU PYLON BATTERY CO LTD

Patent Information

Application Number
CN202411770271.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate and compare the cycle stability of lithium-ion battery anode materials, especially under different cycle testing conditions, and traditional methods usually require destructive analysis, with long and complex cycles.

Method used

By making a battery, a specific short-cycle cycle step test is performed, charging and discharging capacity is recorded, capacity difference and capacity deceleration rate are calculated, and the attenuation rate constant k value is fitted to evaluate and compare the cycle stability of the negative electrode material.

Benefits of technology

This method can non-destructively evaluate the cycle stability of the negative electrode material, shorten the development cycle, provide a method to quickly understand the cycle life performance of the negative electrode material in the battery, and can conduct accelerated aging experiments under different cycle test conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses an evaluation method and a comparison method for the cycling stability of a negative electrode material. The method for evaluating the cycling stability of the negative electrode material comprises the following steps: preparing the negative electrode material to be evaluated into a battery, and recording the initial capacity as C0; carrying out charge-discharge circulation, carrying out constant-current discharge until the cutoff capacity is as follows: Ccutoff = (1-X) * C0, and X is more than 0 and less than or equal to 0.3; counting accumulated charging capacity CCn and discharging capacity DCn after n cycles; obtaining a capacity difference value C = CCn-DCn; xi is set to be equal to X0 + X0 (i-1), and 1 < = i; when C = Ci = Xi * C0, recording the cycle index ni at the moment; when any two different i values are taken, the difference Ci of the two corresponding Ci values and the difference ni of the two corresponding ni values are calculated as Vi = Ci / ni; multiple groups of ni and Vi data are obtained, a linear relation curve of a slope absolute value k is obtained through fitting, and the larger the k value is, the poorer the cycling stability is.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery testing, and in particular to an evaluation method and a comparison method for the cycle stability of negative electrode materials. Background Art

[0002] As a medium for storing energy, lithium-ion batteries have been widely used in the fields of power batteries, photovoltaic energy storage, etc., especially energy storage, which places increasingly higher requirements on cycle life. Taking energy storage batteries with lithium iron phosphate as the positive electrode as an example, the cycle stability of the negative electrode material in the battery determines the key to the cycle life of the battery. Therefore, how to screen out negative electrode materials with more stable performance is the key to achieving a long cycle life of battery products. Usually, when screening materials, the usability of the material is judged by whether the actual number of battery cycles can be achieved. In actual testing, especially for products with a cycle life of more than 10,000 times, the actual situation of more than 10,000 cycles during material evaluation is rare. Taking into account practical applications, usually, the actual cycle is combined with the cycle life model to simulate the cycle life of the battery to judge the cycle life or cycle stability of the material.

[0003] The existing test methods include: Application No. 202311823650.1, a super-linear cycle life prediction method for lithium-ion batteries based on temperature acceleration, which changes the test environment, such as the high-temperature accelerated aging method, and places the batteries in a constant temperature box with a temperature gradient, connected to a test cabinet, and performs charge and discharge cycles at a set rate; based on the cycle data, a capacity degradation model of the number of cycles and the ambient temperature stress factor is created; based on the model, a cycle life curve model under target conditions is obtained. This method has the defect that it cannot perform accelerated aging experiments on lithium-ion batteries under different cycle test conditions, and it predicts the entire battery system and cannot be decomposed into the impact of a single material. For example: Application No. 202111144262.1, a method for predicting the cycle life of lithium iron phosphate batteries, which is a destructive method. Based on the consumption of active lithium by SEI film thickening, the lithium concentration of the negative electrode of the battery after different cycle aging is calibrated by ICP test, and the cycle-active lithium loss ICP model F(x) is established; the active lithium concentration of the lithium iron phosphate battery to be tested is calculated, and the ideal curve model F(x) is input for calculation to obtain the predicted cycle life of the lithium iron phosphate battery. This test method is a destructive analysis method, which requires multiple batches of testing and disassembly of the battery, with a long cycle and a complicated process.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a method for evaluating and comparing the cycle stability of negative electrode materials.

[0006] The present invention is achieved in that: In a first aspect, an embodiment of the present invention provides a method for evaluating the cycle stability of a negative electrode material, comprising: The negative electrode material to be evaluated is made into a battery, and the initial capacity is recorded as C0, and the corresponding number of cycles is n0, where n0=0; Take n0 as the starting point for the cycle life test and set the cycle step conditions: Constant current and constant voltage charging; constant current discharge, the cut-off condition is capacity cut-off, and the discharge cut-off capacity is C 截止 =(1-X)*C0,0<X≤0.3; Record the charge capacity C of each cycle 充1 , C 充2 , C 充3 ……C 充n , C 充n+1 , and the discharge capacity C 放1 , C 放2 , C 放3 ……C 放n , C 放n+1 ; Statistical cycle n times cumulative charging capacity CC n = C 充1 +C 充2 +C 充3 +……+C 充n +C 充n+1 ; Cumulative discharge capacity DC after n cycles n = C 放1 +C 放2 +C 放3 +……+C 放n +C 放n+1 ; The capacity difference after n cycles is △C=CCn-DCn; Let the capacity segmentation factor be X i , X i =X0+X0(i-1), 1≤i, and i is an integer, X0=X / N, N>1; When △C=C i =X i *C0, record the number of cycles ni at this time; Record the difference between the two corresponding Ci values ​​△Ci and the difference between the two corresponding ni values ​​△ni when taking any two different i values, and calculate the capacity deceleration rate Vi=△Ci / △ni; Acquire multiple groups of Vi data corresponding to △ni, and obtain a linear relationship curve between Vi and △ni according to the data fitting, wherein the absolute value k of the slope of the linear relationship curve is the decay rate constant; The larger the k value, the worse the cycling stability.

[0007] In an optional embodiment, X is 0.005 to 0.3, preferably 0.1.

[0008] In an optional embodiment, N is 5 to 20, preferably 10.

[0009] In an optional implementation, the current of the constant current charging process is 0.2~1.5C, and the current of the constant current discharging process is 0.2~1.5C.

[0010] In an optional embodiment, the battery is a battery using lithium iron phosphate as the positive electrode active material, and the charging process is to charge to 3.65V with a constant current, and then charge at a constant voltage of 3.65V, and cut off at 0.05C; Alternatively, the battery is a battery using lithium titanate as the positive electrode active material, and the charging process is to charge at a constant current to 2V, then charge at a constant voltage of 2V, and cut off at 0.02C.

[0011] In an alternative embodiment, the positive electrode active material of the battery is lithium iron phosphate or lithium titanate.

[0012] In an optional embodiment, the negative electrode active material of the battery is an artificial graphite negative electrode material, a natural graphite negative electrode material, a carbon-coated graphite negative electrode material, a silicon-carbon negative electrode material, a silicon-oxygen negative electrode material, a hard carbon negative electrode material or a soft carbon negative electrode material.

[0013] In a second aspect, an embodiment of the present invention provides a method for comparing the cycle stability of different negative electrode materials, including: obtaining k values ​​of different negative electrode materials according to the aforementioned evaluation method under the same parameters, and comparing the k values ​​corresponding to different negative electrode materials. The smaller the k value, the better the cycle stability of the negative electrode material.

[0014] The present invention has the following beneficial effects: In summary, the evaluation method provided by the embodiment of the present invention adopts a non-destructive method from the perspective of material stability, through a specific short-cycle cycle step test, combined with data processing and function fitting, to obtain characteristic parameters of material stability, which are used to judge the material's cycle stability. This method can greatly shorten the development cycle, facilitate R&D personnel to more quickly understand the cycle life performance of the negative electrode material in the developed battery, and provide new ideas and methods for material screening.

[0015] Compared with the prior art, the evaluation method provided by the present invention can perform accelerated aging experiments on lithium-ion batteries under different cycle test conditions without the need for destructive analysis of the batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 is a flow chart of the evaluation method of the present invention; Figure 2 This is the curve diagram obtained by fitting in Example 1; Figure 3 This is the curve diagram obtained by fitting in Example 2; Figure 4 This is the curve diagram obtained by fitting in Example 3; Figure 5 This is the curve diagram obtained by fitting in Example 4; Figure 6 This is the curve diagram obtained by fitting in Example 5; Figure 7 This is the curve diagram obtained by fitting in Example 6. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] like Figure 1 As shown, an embodiment of the present invention provides a method for evaluating the cycle stability of a negative electrode material, comprising: The negative electrode material to be evaluated is made into a battery, and the initial capacity is recorded as C0, and the corresponding number of cycles is n0, where n0=0; Take n0 as the starting point for the cycle life test and set the cycle step conditions: Constant current and constant voltage charging; constant current discharge, the cut-off condition is capacity cut-off, and the discharge cut-off capacity is C 截止 =(1-X)*C0,0<X≤0.3; Record the charge capacity C of each cycle 充1 , C 充2 , C 充3 ……C 充n , C 充n+1 , and the discharge capacity C 放1 , C 放2 , C 放3 ……C 放n , C 放n+1 ; Statistical cycle n times cumulative charging capacity CC n = C 充1 +C 充2 +C 充3 +……+C 充n +C 充n+1 ; Cumulative discharge capacity DC after n cycles n = C 放1 +C 放2 +C 放3 +……+C 放n +C 放n+1 ; The capacity difference after n cycles is △C=CCn-DCn; Let the capacity segmentation factor be X i , X i =X0+X0(i-1), 1≤i, and i is an integer, X0=X / N, N>1; When △C=C i =X i *C0, record the number of cycles ni at this time; Record the difference between the two corresponding Ci values ​​△Ci and the difference between the two corresponding ni values ​​△ni when taking any two different i values, and calculate the capacity deceleration rate Vi=△Ci / △ni; Acquire multiple groups of Vi data corresponding to △ni, and obtain a linear relationship curve between Vi and △ni according to the data fitting, wherein the absolute value k of the slope of the linear relationship curve is the decay rate constant; The larger the k value, the worse the cycling stability.

[0020] Optionally, X is 0.005-0.3 (for example, 0.005, 0.01, 0.05, 0.1, 0.2 or 0.3), preferably 0.1.

[0021] Optionally, N is 5 to 20 (for example, 5, 8, 10, 15 or 20), preferably 10.

[0022] Optionally, a battery with a battery capacity of 0.5~30Ah is used for evaluation, and the current during the charging process or the discharging process is 0.2~1.5C. The charging and discharging current is selected according to the specific battery capacity, and the specific reference can be made to the charging current and discharging current of the existing battery with the same capacity.

[0023] Optionally, the current of the constant current charging process is 0.2~1.5C, and the current of the constant current discharging process is 0.2~1.5C.

[0024] Specifically, the battery is a 5Ah capacity battery with lithium iron phosphate as the positive electrode active material, and the charging process is to charge at a constant current to 3.65V, then charge at a constant voltage of 3.65V, and cut off at 0.05C; The battery is a 5Ah capacity battery using lithium titanate as the positive electrode active material. The charging process is to charge at a constant current to 2V, then charge at a constant voltage of 2V, and cut off at 0.02C.

[0025] Usually, the battery is charged or discharged at a C rate. For example, if the rated capacity of the battery is 5Ah, the C rate current setting is 1C current is 5A, 0.5C current is 2.5A, 0.05C current is 0.25A, and 0.02C current is 0.1A. Then 0.2~1.5C corresponds to 0.1~7.5A.

[0026] Optionally, the positive electrode active material of the battery includes but is not limited to a lithium iron phosphate battery or a lithium titanate battery. The crystal structure stability of lithium iron phosphate and lithium titanate is good, and will not interfere with the evaluation results, and the evaluation results are more reliable. It should be noted that in addition to lithium iron phosphate and lithium titanate, other positive electrode materials with good crystal structure stability can also be selected.

[0027] Optionally, the negative electrode active material of the battery is an artificial graphite negative electrode material, a natural graphite negative electrode material, a carbon-coated graphite negative electrode material, a silicon-carbon negative electrode material, a silicon-oxygen negative electrode material, a hard carbon negative electrode material or a soft carbon negative electrode material.

[0028] An embodiment of the present invention provides a method for comparing the cycle stability of different negative electrode materials, comprising: obtaining k values ​​of different negative electrode materials under the same parameters according to the evaluation method provided by the present invention, comparing the k values ​​corresponding to different negative electrode materials, and the negative electrode material with a smaller k value has better cycle stability.

[0029] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0030] Example 1 Negative electrode material: artificial graphite A (material 1), the negative electrode material is mixed with a conductive agent (Super P, conductive carbon black), a thickener (CMC, sodium carboxymethyl cellulose), and a binder (SBR, styrene-butadiene rubber) in a mass ratio of 95:1.5:1.5:2.0 to make a slurry, which is then coated on a copper foil to obtain a negative electrode sheet; Positive electrode material: lithium iron phosphate. The positive electrode material, conductive agent (conductive carbon black super P), and adhesive (PVDF, polyvinylidene fluoride) are made into a slurry in a mass ratio of 97:1.2:1.8 and coated on aluminum foil to obtain a positive electrode sheet.

[0031] The positive electrode sheet, the negative electrode sheet and the separator (PP) are assembled into a laminated soft-pack battery with a capacity of about 5Ah, which has 10 layers of positive electrode sheets and 11 layers of negative electrode sheets.

[0032] The battery is charged at 4.5901A and discharged at 4.5901A. C0=4.5901, X=0.1, N=10. The calculation process data is shown in Table 1: Table 1 Calculation process data of Example 1

[0033] The data in Table 1 are fitted to obtain a curve as Figure 2 As shown, the k value obtained is 0.0113.

[0034] Example 2 This embodiment is basically the same as Embodiment 1, except that the negative electrode material is artificial graphite B (material 2).

[0035] The battery is charged at 4.6001A and discharged at 4.6001A. C0=4.6001, X=0.1, N=10. The calculation process data is shown in Table 2: Table 2 Calculation process data of Example 2

[0036] The data in Table 1 are fitted to obtain a curve as Figure 3 As shown, the k value obtained is 0.0172.

[0037] Example 3 This embodiment is basically the same as Embodiment 1, except that the negative electrode material is artificial graphite C (material 3).

[0038] The battery is charged at 4.59369A and discharged at 4.59369A. C0=4.59369, X=0.1, N=10. The calculation process data is shown in Table 3: Table 3 Calculation process data of Example 3

[0039] The data in Table 1 are fitted to obtain a curve as Figure 4 As shown, the k value obtained is 0.0196.

[0040] Example 4 This embodiment is basically the same as the first embodiment, except that the battery has 12 positive electrode sheets and 13 negative electrode sheets.

[0041] The battery is charged at 5.280A and discharged at 5.280A. C0=5.280, X=0.01, N=10. The calculation process data is shown in Table 4: Table 4 Calculation process data of Example 4

[0042] The data in Table 1 are fitted to obtain a curve as Figure 5 As shown, the k value obtained is 0.0998.

[0043] Example 5 This embodiment is basically the same as the embodiment 2, except that the battery has 12 layers of positive electrode sheets and 13 layers of negative electrode sheets.

[0044] The battery is charged at 5.256A and discharged at 5.256A. C0=5.256, X=0.01, N=10. The calculation process data is shown in Table 5: Table 5 Calculation process data of Example 5

[0045] The data in Table 1 are fitted to obtain a curve as Figure 6 As shown, the k value is 0.2466.

[0046] Example 6 This embodiment is basically the same as the embodiment 3, except that the battery has 12 layers of positive electrode sheets and 13 layers of negative electrode sheets. The battery is charged at 5.066A and discharged at 5.066A. C0=5.066, X=0.01, N=10. The calculation process data is shown in Table 6: Table 6 Calculation process data of Example 6

[0047] The data in Table 1 are fitted to obtain a curve as Figure 7 As shown, the k value is 0.3182.

[0048] Some implementation parameters and calculation results of Examples 1 to 6 are summarized in Table 7.

[0049] Table 7 Implementation parameters and k values ​​of various embodiments

[0050] From the statistical results of Table 7, it can be concluded that the k value of each material 1 is smaller than the k value of material 2 and smaller than the k value of material 3. This shows that the cycle stability of material 1 is better than that of material 2, and the cycle stability of material 2 is better than that of material 3. Compared with Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6, X is selected as 0.01. The results show that the k value of material 1 is smaller than the k value of material 2 and smaller than the k value of material 3, which is consistent with the result of X=0.1, and the number of charge and discharge verifications is further reduced, further shortening the verification cycle. This fully shows that the verification method is reliable.

[0051] Verification Example The soft-pack batteries prepared in Examples 1 to 3 were respectively subjected to cycle performance tests with reference to "Cycle Life Requirements and Test Methods for Power Batteries for Electric Vehicles (GB / T 31484-2015)": The test environment is a high temperature of 45°C. a: Discharge at 1C constant current, cut-off voltage is 2.5V; b: Leave for 30 minutes; c: Charge at 1C constant current to 3.65V, then charge at 3.65V constant voltage, stop charging when the current drops to 0.05C; d: Leave for 30 minutes; e: Discharge at 1C, cut-off voltage is 2.5V, record the discharge capacity; f: Continuously charge and discharge according to b~e. If the discharge capacity is less than 80% of the initial capacity, terminate the test and record the number of cycles in Table 8.

[0052] Table 8 Cyclic performance test results of each material

[0053] It can be seen from the results in Table 8 that the cyclic stability of material 1 is better than that of material 2, and the cyclic stability of material 2 is better than that of material 3. This result is consistent with the evaluation result of the embodiment of the present invention, indicating that the evaluation method provided by the present invention is reliable.

[0054] In summary, the evaluation method provided by the embodiment of the present invention adopts a non-destructive method from the perspective of material stability, and obtains characteristic parameters of material stability through specific short-cycle cycle step tests, combined with data processing and function fitting, to judge the material's cycle stability. This method can greatly shorten the development cycle, facilitate R&D personnel to more quickly understand the cycle life performance of the negative electrode material in the developed battery, and provide new ideas and methods for material screening.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for evaluating the cycle stability of a negative electrode material, characterized in that: include: The negative electrode material to be evaluated is made into a battery, and the initial capacity is recorded as C0, and the corresponding number of cycles is n0, where n0=0; Take n0 as the starting point for the cycle life test and set the cycle step conditions: Constant current and constant voltage charging; constant current discharge, the cut-off condition is capacity cut-off, and the discharge cut-off capacity is C 截止 =(1-X)*C0,0<X≤0.3; Record the charge capacity C of each cycle 充1 , C 充2 , C 充3 ……C 充n , C 充n+1 , and the discharge capacity C 放1 , C 放2 , C 放3 ……C 放n , C 放n+1 ; Statistical cycle n times cumulative charging capacity CC n = C 充1 +C 充2 +C 充3 +……+C 充n +C 充n+1 ; Cumulative discharge capacity DC after n cycles n = C 放1 +C 放2 +C 放3 +……+C 放n +C 放n+1 ; The capacity difference after n cycles is △C=CCn-DCn; Let the capacity segmentation factor be X i , X i =X0+X0(i-1), 1≤i, and i is an integer, X0=X / N, N>1; When △C=C i =X i *C0, record the number of cycles ni at this time; Record the difference between the two corresponding Ci values ​​△Ci and the difference between the two corresponding ni values ​​△ni when taking any two different i values, and calculate the capacity deceleration rate Vi=△Ci / △ni; Acquire multiple groups of Vi data corresponding to △ni, and obtain a linear relationship curve between Vi and △ni according to the data fitting, wherein the absolute value k of the slope of the linear relationship curve is the decay rate constant; The larger the k value, the worse the cycling stability.

2. The evaluation method according to claim 1, characterized in that: X is 0.005 to 0.3, preferably 0.

1.

3. The evaluation method according to claim 1, characterized in that: N is 5 to 20, preferably 10.

4. The evaluation method according to claim 1, characterized in that: The current of the constant current charging process is 0.2~1.5C, and the current of the constant current discharging process is 0.2~1.5C.

5. The evaluation method according to claim 4, characterized in that: The battery is a battery with lithium iron phosphate as the positive electrode active material. The charging process is to charge at a constant current to 3.65V, then charge at a constant voltage of 3.65V, and cut off at 0.05C; Alternatively, the battery is a battery using lithium titanate as the positive electrode active material, and the charging process is to charge at a constant current to 2V, then charge at a constant voltage of 2V, and cut off at 0.02C.

6. The evaluation method according to claim 1, characterized in that: The positive electrode active material of the battery is lithium iron phosphate or lithium titanate.

7. The evaluation method according to claim 1, characterized in that: The negative electrode active material of the battery is an artificial graphite negative electrode material, a natural graphite negative electrode material, a carbon-coated graphite negative electrode material, a silicon-carbon negative electrode material, a silicon-oxygen negative electrode material, a hard carbon negative electrode material or a soft carbon negative electrode material.

8. A method for comparing the cycle stability of different negative electrode materials, characterized in that: include: Under the same parameters, different negative electrode materials are subjected to the evaluation method as described in any one of claims 1 to 6 to obtain k values, and the k values ​​corresponding to different negative electrode materials are compared. The negative electrode material with a smaller k value has better cycle stability.

Citation Information

Patent Citations

  • Lithium iron phosphate battery cycle life prediction method

    CN113884929A

  • Lithium ion battery super-linear cycle life prediction method based on temperature acceleration

    CN117970120A

Cited By

  • Electrode material performance evaluation method, device and system and storage medium

    CN121068702A